Crime Reporting Through Social Media: Potential Opportunities in Community Policing - Washington, Kimberly (2020)
The popularity and usage of social media over the years has increased. Due to this increase there has now been an influx of information shared on a global platform. This information that has been shared can be as superficial as daily activities, food eaten or as sensitive as graphic crimes committed. The Perceived Social Media Anonymity Effect is a concept that I am introducing and seek to explore. It is based on the premise that allows one to relinquish the fear of being in large crowds and speaking up when crimes have been committed while also being able to seek solitude among numbers on a social media platform where it appears easier to report and inform. This concept stems from the Bystander Effect. Darley & Latane (1968) states that the Bystander Effect refers to the phenomenon surrounding the passivity of onlookers’ willingness to help or intervene when faced with critical situations where others are being harmed. This study reviewed literature and high-profile social media exposure cases and analyzed the following questions: To what extent is there a nexus between non-reporting of crimes and reporting on social media? Furthermore, what are the perceived factors an individual reports that they take into account when determining whether to post or share videos of crimes on social media platforms and/or not reporting to police? To explore these issues, the public cases of Eric Garner, Laquan McDonald and Kenneka Jenkins were used to determine the impact of social media and its usage in a way of spreading information to the general public and at times used as a catalyst for social change. Information from a range of sources including local and national newspaper articles, media interviews, Chicago Police Department and the New York Police Department are synthesized and analyzed. This study concludes by reviewing implications and findings and recommendations for future study. The popularity and usage of social media over the years has increased. Due to this increase there has now been an influx of information shared on a global platform. This information that has been shared can be as superficial as daily activities, food eaten or as sensitive as graphic crimes committed. The Perceived Social Media Anonymity Effect is a concept that I am introducing and seek to explore. It is based on the premise that allows one to relinquish the fear of being in large crowds and speaking up when crimes have been committed while also being able to seek solitude among numbers on a social media platform where it appears easier to report and inform. This concept stems from the Bystander Effect. Darley & Latane (1968) states that the Bystander Effect refers to the phenomenon surrounding the passivity of onlookers’ willingness to help or intervene when faced with critical situations where others are being harmed. This study reviewed literature and high-profile social media exposure cases and analyzed the following questions: To what extent is there a nexus between non-reporting of crimes and reporting on social media? Furthermore, what are the perceived factors an individual reports that they take into account when determining whether to post or share videos of crimes on social media platforms and/or not reporting to police? To explore these issues, the public cases of Eric Garner, Laquan McDonald and Kenneka Jenkins were used to determine the impact of social media and its usage in a way of spreading information to the general public and at times used as a catalyst for social change. Information from a range of sources including local and national newspaper articles, media interviews, Chicago Police Department and the New York Police Department are synthesized and analyzed. This study concludes by reviewing implications and findings and recommendations for future study